Meso-structure construction and effective modulus simulation of PBXs. Issue 3 (2nd July 2020) - Kang, Ge; Ning, Youjun; Chen, Pengwan; Ni, Kesong
ABSTRACT: The polymer-bonded explosive (PBX) is a kind of multi-phase composite consisting of the polymeric binder and embedded energetic particles, in which the particle volume fraction (PVF) is often higher than 90%. In the present work, by using the Voronoi-polygon generation method along with the concept of gradation to generate Voronoi particles with given gradation, and with further operations including modification, shrinking, smoothing, etc. to the particles, a new meso-structure construction method for PBXs is proposed. The constructed meso-structures possess good gradation relationship and have high PVFs (94.99% in maximum) simultaneously. The strict periodicity on the boundaries of the meso-structure can also be achieved. To verify the constructed PBX meso-structures, the numerical manifold method (NMM) is used to simulate the effective modulus of the constructed meso-structures by considering different influencing factors such as the size of meso-structure, PVF, gradation, and initial defects, etc. The simulation results are analyzed qualitatively, and the causes of differences between the simulation results and available experimental results or other numerical results are discussed. The validity of the proposed method for the construction of PBX meso-structures is verified. This work also provides foundations for the further numerical studies of the mechanical and thermal behaviors of PBXs at the mesoscale.